Uni and biaxial impact behavior of double-gated nanoclay-reinforced polypropylene injection moldings - Pettarin, Valeria (2012)
Polypopylene/nanoclay three-dimensional parts were produced without intermediate steps by direct injection molding to explore the influence of flow features and nanoclay incorporation in their impact performance. The nanocomposite was obtained by direct compounding of commercial PP with nanoclay masterbatch. The as-molded morphology was analyzed by X-ray and TEM analyses in terms of skin-core structure and nanoclay particle dispersion. The nanoclay particles induced the reduction of β-form spherulites, a known toughener. The impact behavior was assessed in tensile and biaxial modes. The PP nanocomposite molding toughness was practically unaffected by the processing melt temperature and flow rate. Conversely the nanoclay presence is influent in the impact performance. Under biaxial stress impact, the regions close to weld lines are tougher than the bulk and the fracture develops with main crack paths along the flow direction and the weld line. Cracking along the weld line results from less macromolecular interpenetration and chain entanglement, and unfavorable nanoparticle orientation. It seems that a failure mechanism which involves nanoclay delamination and multiple matrix crazing explains the toughening of PP in the directions where the nanoparticle orientation with respect to loading is adequate